P101: The development of entrustable professional activity reference cards to support the implementation of Competence by Design in emergency medicine. (May 2019) - Stoneham, E.; Witt, L.; Paterson, Q.; Martin, L.; Thoma, B.
Abstract : Innovation Concept : Competence by Design (CBD) was implemented nationally for Emergency Medicine (EM) residents beginning training in 2018. One challenge is the need to introduce residents to Entrustable Professional Activities (EPAs) that are assessed across numerous clinical rotations. The Royal College's resources detail these requirements, but do not map them to specific rotations or present them in a succinct format. This is problematic as trainees are less likely to succeed when expectations are unclear. We identified a need to create practical resources that residents can use at the bedside.Methods : We followed an intervention mapping framework to design two practical, user-friendly, low-cost, aesthetically pleasing resources that could be used by residents and observers at the bedside to facilitate competency-based assessment.Curriculum, Tool or Material : First, we designed a set of rotation- and stage-specific EPA reference cards for the use of residents and observers at the bedside. These cards list EPAs and clinical presentations likely to be encountered during various stages of training and on certain rotations. Second, we developed a curriculum board to organize the EPA reference cards by stage based upon our program's curriculum map. The curriculum board allows residents to view the program's curriculum map and the EPAs associated with each clinical rotation at a glance. It also contains hooks to hang and store extra cards in an organized manner.Conclusion : We believe that these practical and inexpensive tools facilitated our residency program's transition to competency-based EPA assessments. Anecdotally, the residents are using the cards and completing the suggested rotation-specific EPAs. We hope that the reference cards and curriculum board will be successfully incorporated into other residency programs to facilitate the introduction of their EPA-based CBD assessment system.